Managerial Forecasts and European Multinational Company Reporting - Gray, S. J. (Journal of International Business Studies, 1978)
This article examines the nature and extent of disclosure of forecasts by EEC multinationals. The overall level of disclosure would seem to be low and largely of a qualitative nature. While there are some intercountry differences in the European context, these do not, in general, provide support for the hypothesis that the extent of disclosure is correlated with national equity market efficiency. An attempt is made to explain this situation and to examine current developments bearing on this controversial disclosure issue.